2000
DOI: 10.1038/sj.bmt.1702603
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A-related cerebral vasculopathy

Abstract: Summary:The use of cyclosporin A has been associated with several side-effects, including neurotoxicity. The mechanism of toxicity is not well known. We report two patients treated with cyclosporin A who developed lesions in the cerebral white matter associated with abnormally elevated cerebral blood flow velocities on transcranial doppler ultrasound and abnormal vascular appearance on magnetic resonance angiography. Bone Marrow Transplantation (2000) 26, 801-804. Keywords: cyclosporin A; toxicity; vasospasm; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In our patients with cerebrovascular disease, however, the distribution of infarcts or ICH was different from that in patients with neurotoxicity [13,14,15]. In addition, cyclosporine was already withheld at the onset of attacks in 2 of the 4 patients with cerebrovascular disease due to systemic infection or poor general condition.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our patients with cerebrovascular disease, however, the distribution of infarcts or ICH was different from that in patients with neurotoxicity [13,14,15]. In addition, cyclosporine was already withheld at the onset of attacks in 2 of the 4 patients with cerebrovascular disease due to systemic infection or poor general condition.…”
Section: Discussionmentioning
confidence: 96%
“…In both patients, seizures occurred following administration of these drugs and resolved after their withdrawal. Although the mechanism of neurotoxicity is not completely known, cyclosporine has been reported to cause vasoconstriction and endothelial damage [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…27 MRI studies of PRES patients have also revealed characteristics of reversible vasogenic edema congruent with our findings in the present ARE model; hyperintensities are seen in T 2 w MR images along with concomitant increases in the ADC, most prominently in the occipital or occipito-parietal lobes, 5,42 and a narrowing or beaded appearance for the vessels in MRA, reflecting an underlying vasospasm and/or vasoconstriction. 40,41,43 The distribution of lesions in the present ARE model was primarily diffuse, but tended to favor the occipito-parietal area (Bregma À4 to À6 mm). Although it is not clearly identified, both PRES and ARE are likely to be based on the similar pathogenesis (endothelial damage) due to hypertension and CsA.…”
Section: Discussionmentioning
confidence: 99%
“…CA and MRA demonstrate focal vasoconstriction, focal vasodilation, string-of-beads appearance, and vessel pruning, undoubtedly reflecting endothelial dysfunction (increased and decreased vessel tone) or reduced flow. 21,24,37,40,46,47,[94][95][96] Diffuse vasoconstriction is also present. 24 These features have been noted in hypertensive as well as nonhypertensive patients and have been shown to reverse.…”
Section: Evidence Of Hypoperfusion In Presmentioning
confidence: 99%